Evaluation of antibacterial property of anthyocyanin extracted from brassica oleracea against gram positive and gram negative bacteria by using erythromycin as a standard drug. - Tallam, Anil Kumar; Sahithi, Alapati; Nuli, Mohana Vamsi (International Journal of Indigenous Herbs and Drugs, 2023)
Anthocyanin was extracted from Brassica oleracea and identified by UV and TLC.The benzene test initially helps us to identify Anthocyanin in residue. Crystals were purified by recrystallization from ether. Acetone –petroleum ether extraction resulted in higher crude Anthocyanin yield than hexane extraction The compounds were tested against two microorganisms namely E. coli (gram-ve) and bacillus (gram+ve) and the compounds showed significant activity against two species. Test sample one Showed significant activity with zone of inhibition (18.21mm). When compared to standard Erythromycin with zone of inhibition (20.83mm) at 100,200,400mg/ml against E. coli organism. Test sample two Showed significant activity with zone of inhibition (15.56mm) when compared to standard Erythromycin with zone of inhibition at (100,200,400mg/ml) against Bacillus.